Zacharij Niemcevski – professor of higher mathematics at the Vilnius university (1797–1820) - Gečiauskas, Evaldas (Lietuvos matematikos rinkinys, 2023)
Zacharij Niemcevski (1766–1820) was a professor of higher mathematics at the Vilnius university in the period from 1797 until 1820. He was a member correspondent of Societe Academique des sciences and Academie Imperial des Sciences de Turin. Niemcevski tought differential and integral calculus by the tracktate of S.F. Lacroix, analytic geomety – by J.B. Biot, and mechanics – by L.B. Francoeur.  His investigations on the Lithuanian language was published in the tractate of K. Malte Brun.
Keywords: professor of mathematics Z. Niemcevski